Uso de resíduos de madeiras e frutos da amazônia para o cultivo In Vitro do cogumelo comestível shiitake - De Aguiar, Lorena Vieira Bentolila; Sales-Campos, Ceci; De Carvalho, Cristiane Suely Melo; De Almeida Minhoni, Marli Teixeira [UNESP]; De Andrade, Meire Cristina Nogueira (My University, 2013)
Local abundant residues with low or without commercial value with potential to make the production of edible mushrooms economically viable in any region of Brazil must be employed for cultivation. Thus, the radial mycelial growth of LED 20 strain of Lentinula edodes (Berk.) Pegler was verified in culture media prepared with extract of regional residues by using substrates based on Protium puncticulatum, Cariniana micrantha and Caryocar glabum sawdust, supplemented with 20% of grinded residues from the barks of the fruits of Astrocaryum aculeatum and Theobroma grandiflorum. Residues from eucalyptus (Eucalyptus spp.) sawdust and wheat bran (Triticum aestivum L.) were used as witness because they are commonly used in the cultivation of L. edodes. The experimental design used was totally randomized, in 4×3 factorial scheme, totalizing 12 treatments with five repetitions, being that each repetition corresponded to a Petri dish, adding up a total of 60 dishes, which were incubated under 25°C. The diameter of the colony was daily evaluated during seven days of incubation. After that period, it was verified that media prepared with P. puncticulatum extract, whose supplementation with both brans was favorable for fungic development, presented some of the highest averages of mycelial growth of LED 20 strain of L. edodes, confirming the potential of those residues.
Use of wood res idues and fruit from amazon for the In Vitro cultiva tion of edible mushr oom shiitake